2016
DOI: 10.3389/fimmu.2016.00422
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Factors Galectin-9 and Interferon-Gamma Synergize to Induce Expression of Rate-Limiting Enzymes of the Kynurenine Pathway in the Mouse Hippocampus

Abstract: Elevated levels of circulating pro-inflammatory cytokines are associated with symptomology of several psychiatric disorders, notably major depressive disorder. Symptomology has been linked to inflammation/cytokine-dependent induction of the Kynurenine Pathway. Galectins, like pro-inflammatory cytokines, play a role in neuroinflammation and the pathogenesis of several neurological disorders but without a clearly defined mechanism of action. Their involvement in the Kynurenine Pathway has not been investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 68 publications
(90 reference statements)
3
31
0
Order By: Relevance
“…Interestingly, Ido1 induction was blocked by Desip in the circulation (murine PBMCs, PBMC −T s, T cells and human PBMCs) and the brain (murine hippocampi, microglia and astrocytes). Using organotypic hippocampal slice cultures (OHSCs), we found that IFNγ-induced Ido1 and Ido2 expression was blocked by Desip, and furthermore, that our previously described synergy between IFNγ and either Dex (Brooks et al, 2016b) or galectin-9 (Brooks et al, 2016a) to accentuate specific Ido1 and Ido2 transcripts were blocked by Desip.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Interestingly, Ido1 induction was blocked by Desip in the circulation (murine PBMCs, PBMC −T s, T cells and human PBMCs) and the brain (murine hippocampi, microglia and astrocytes). Using organotypic hippocampal slice cultures (OHSCs), we found that IFNγ-induced Ido1 and Ido2 expression was blocked by Desip, and furthermore, that our previously described synergy between IFNγ and either Dex (Brooks et al, 2016b) or galectin-9 (Brooks et al, 2016a) to accentuate specific Ido1 and Ido2 transcripts were blocked by Desip.…”
Section: Introductionmentioning
confidence: 81%
“…C57BL/6J pups were used to generate OHSCs as previously described (Brooks et al, 2016a; Brooks et al, 2016b). Hippocampi were sliced and placed onto membrane inserts in 6-well plates containing medium (50% Eagle’s MEM, 25% HBSS, 25% heat-inactivated horse serum, penicillin/streptomycin, HEPES, 0.5% D-glucose).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations